Guest

SecA-tanA/secA pulse tanA equal to 1-2secAtanA pulse 2tans squareA

SecA-tanA/secA pulse tanA equal to 1-2secAtanA pulse 2tans squareA

Grade:11

1 Answers

Nishant Vora IIT Patna
askIITians Faculty 2467 Points
5 years ago
use the fact that sec^2 – tan^2 = 1

hence, (secA + tanA)(secA - tanA) = 1
=>(secA + tanA) = 1/(secA - tanA)

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free